RAD18 directs DNA double-strand break repair by homologous recombination to post-replicative chromatin - Palek, Matous; Palkova, Natalie; consortium CZECANCA; Kleiblova, Petra; Kleibl, Zdenek; Macurek, Libor (Nucleic acids research, 2024)
RAD18 is an E3 ubiquitin ligase that prevents replication fork collapse by promoting DNA translesion synthesis and template switching. Besides this classical role, RAD18 has been implicated in homologous recombination; however, this function is incompletely understood. Here, we show that RAD18 is recruited to DNA lesions by monoubiquitination of histone H2A at K15 and counteracts accumulation of 53BP1. Super-resolution microscopy revealed that RAD18 localizes to the proximity of DNA double strand breaks and limits the distribution of 53BP1 to the peripheral chromatin nanodomains. Whereas auto-ubiquitination of RAD18 mediated by RAD6 inhibits its recruitment to DNA breaks, interaction with SLF1 promotes RAD18 accumulation at DNA breaks in the post-replicative chromatin by recognition of histone H4K20me0. Surprisingly, suppression of 53BP1 function by RAD18 is not involved in homologous recombination and rather leads to reduction of non-homologous end joining. Instead, we provide evidence that RAD18 promotes HR repair by recruiting the SMC5/6 complex to DNA breaks. Finally, we identified several new loss-of-function mutations in RAD18 in cancer patients suggesting that RAD18 could be involved in cancer development.
Keywords: histony; 53BP1; Homologous Recombination; Tumor Suppressor p53-Binding Protein 1; Recombinational DNA Repair; Ubiquitin-Protein Ligases; ubikvitinligasy; DNA vazebné proteiny; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; Ubiquitination; rekombinační oprava DNA; ubikvitinace; homologní rekombinace; chromatin; proteiny buněčného cyklu; oprava DNA spojením konců; oprava DNA; Chromatin; DNA Repair; DNA End-Joining Repair; lidé; Humans; replikace DNA; Histones; DNA Replication; Cell Cycle Proteins; DNA-Binding Proteins